(untitled) (Al-Aasar, 2025)
The research highlights how classical and modern scholars have presented the life of the Prophet Muhammad ﷺ through diverse scholarly traditions. It begins by emphasizing the centrality of the Prophet’s ﷺ life as a guiding model for Muslims and underscores the long-standing scholarly commitment to portraying his biography in ways that inspire love, understanding, and moral motivation.The significance of the study lies in its exploration of multiple literary methods, particularly the hadith-based, juristic, theological, and evidence-driven styles found in al-Bayhaqī’s work, and the simple, accessible, devotional, and well-referenced approach of Tawakklī. By comparing these two works, the research demonstrates how each reflects the intellectual needs of its time while maintaining authenticity and scholarly rigor.The study concludes that both classical and modern Sīrah scholars employed valuable and diverse literary techniques that remain highly relevant today. These methods can be effectively adapted to address contemporary intellectual and moral challenges, provided that authenticity, clarity, and reliable sources remain central to Sīrah writing.